2015
DOI: 10.1177/1742271x14568608
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint effusion and its relationship with perceived disability assessed using musculoskeletal ultrasound and a patient-reported disability index

Abstract: The relationship between effusion of the temporomandibular joint (TMJ) and patient-reported disability is poorly researched. This pilot study explored the link between TMJ inflammation as measured by ultrasound and patient disability assessed by the Steigerwald Maher TMD Disability Index (SMTDI). The study design used a prospective correlational approach involving a sample with TMJ dysfunction (TMD). Twenty-four patients were recruited from the European School of Osteopathy and a Kent dental practice. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…An assessment of the joint space size, likewise in our study, has recently been proposed as an alternative to the direct method where the medial part of the joint is obscured by skeletal components (Klatkiewicz et al 2018). According to certain authors, the size of the TMJ space correlates to the volume of the exudate (Bas et al 2011;Johnston et al 2015). However, as reported in our present study, the joint space width does not correlate with articular disc stiffness.…”
Section: Discussionsupporting
confidence: 59%
“…An assessment of the joint space size, likewise in our study, has recently been proposed as an alternative to the direct method where the medial part of the joint is obscured by skeletal components (Klatkiewicz et al 2018). According to certain authors, the size of the TMJ space correlates to the volume of the exudate (Bas et al 2011;Johnston et al 2015). However, as reported in our present study, the joint space width does not correlate with articular disc stiffness.…”
Section: Discussionsupporting
confidence: 59%
“…A recent study by Johnston et al ( 116 ) explored the link between TMJ inflammation as measured by US and patient disability as assessed by the Steigerwald Maher TMD Disability Index (SMTDI). This is the first study in which capsular width was integrated into a functional disability questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Johnston et al assessed the association between TMJ inflammation as measured by ultrasound and patient disability assessed by the Steigerwald Maher TMD Disability Index (SMTDI). The authors reported that greater capsular widths were found to be significant predictors of SMTDI scores [ 3 ]. Although the relationship between functional disability of mandible and capsular width has not been determined in this study, both maximum mouth opening and capsular width significantly correlated with pain scores.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of TMD include muscle and joint pain, TMJ sounds, and limitations in the mandibular movements, often accompanied by tinnitus and headache. Facial pain localized in the TMJ is often attributed to inflammation of the synovium, which causes synovial effusion [ 2 , 3 ]. In general, panoramic radiography, computed tomography (CT), and magnetic resonance imaging (MRI) have been widely employed for diagnostic imaging examinations of the TMJ.…”
Section: Introductionmentioning
confidence: 99%